Implementation of Authentic Leadership Attitudes to Tutors at Community Learning Center (CLC) - Irvansyah, Adi; Sumardjo, Sumardjo; Syah, Rahmat (Edukasi, 2021)
Current research intends to explore authentic leadership's role in the classroom's learning management process and motivation. The object of this research is PKBM An-Nur in Sukamakmur Bogor. The research instrument used interviews and direct observation. The results showed that authentic leadership affects work involvement and affective well-being related to management in PKBM An-Nur. Authentic leadership shows results in the expected direction, namely tutor awareness in teaching and building teamwork in PKBM organizations. Fatigue negatively affects performance and well-being, whereas engagement predicts well-being positively. Quantitative excess is positively associated with attention and burnout. Authentic leadership shows an indirect effect on all outcomes. Quantitative advantages also mediate the relationship between Authentic leadership and engagement and fatigue and sincerity of being a PKBM tutor.